Peran Otoritas Jasa Keuangan dalam Pembentukan Pedoman Teknis Pembiayaan Berbasis Kekayaan Intelektual bagi Bank - Muhammad Daniel Auliaulloh; Lastuti Abubakar; Tri Handayani (Jurnal Interpretasi Hukum, 2024)
The government presents an intellectual property-based financing mechanism through the regulation of Government Regulation Number 24 of 2022 concerning the Creative Economy. The regulation comes as a form of government support for creative economy players to advance the creative economy sector so that it can drive the national economy. The provision opens opportunities for creative economy players to obtain funding in order to build a business from government funds or bank and non-bank financial institutions. In accepting intellectual property as collateral, banks need to fulfill the obligation to conduct business verification, verification of intellectual property certificates, and assessment of intellectual property to be used as collateral. These obligations need to be regulated in a provision of technical guidelines for accepting intellectual property as financing collateral. The development of the technical guidelines needs to be done immediately considering that the regulation is a form of the implementation of the bank's prudential principle as the main principle of the banking sector. The position of the technical guidelines for financing based on intellectual property as financing collateral is to ensure the certainty of the bank in carrying out the financing. The problem arises when banks do not have the authority to make the technical guidelines themselves. Thus, the role of the Financial Services Authority as the banking sector regulator is required. The Financial Services Authority needs to exercise its authority as a regulator in preparing technical guidelines for intellectual property-based financing as an implementing regulation for banks. However, to be able to first create certainty for banks in accepting intellectual property as collateral, OJK can include intellectual property as collateral that can be calculated as a deduction in the calculation of PPKA by amending the Financial Services Authority Regulation Number 40/POJK.03/2019 concerning Asset Quality Assessment of Commercial Banks.